Intergenerational income mobility in Canada: Research highlights from two recent studies - Yuri Ostrovsky (Economic and Social Reports)
This article summarizes findings from an upcoming study in American Economic Journal: Applied Economics that compares absolute intergenerational income mobility rates – the fraction of adult children in the population whose income is higher than that earned by their parents at the same age, in the United States, Canada, the United Kingdom, the Netherlands, Norway, Sweden and Finland. This article also discusses the findings of a pilot study in Measuring Distribution and Mobility of Income and Wealth which examines the impact of parental education on the transmission of income between generations using census data from the Intergenerational Income Database.